Propiedad intelectual en la industria de la moda (2017)
"The fashion industry, in theory, is covered by the protection granted by the Colombian State through the rights of intellectual property (copyright and industrial property), however in analyzing the current arid jurisprudence it can be concluded that fashion is not given the same level of protection as other creative industries, namely that the law protects ""artistic"" objects, but not ""utilitarian"" objects. This article presents a brief review of the existing international intellectual property system discussed during the seminar on Law and Globalization at The Portuguese Catholic University, Porto. Some protection mechanisms provided by Colombian legislation for fashion designs, the difficulty of their application and the need to directly regulate this branch of the creative industry to encourage a growing sector in Colombia are discussed"